The Effect of Metal Filler on the Mechanical Performance of Epoxy Resin Composites - Bhavith K; Prashanth Pai M; Sudheer M; Ramachandra C G; Maruthi Prashanth B H; Kiran Kumar B (Engineering Proceedings)
It is a common practice in the plastics industry to compound polymers with fillers to reduce the manufacturing cost and/or attain desired properties. By combining different fillers with various polymer matrices, polymer composites can be tailored to achieve property combinations which cannot easily be obtained from either the polymer matrices or the reinforcements alone. In the past decades, different metallic (Cu, Al, Steel, etc.) and ceramic fillers (SiC, Al2O3, CuO, TiC, TiO2, TiN, ZrO2, ZnO, ZnF2, SiO2, etc.) have been used as reinforcements in composite preparation because of their effectiveness in reinforcing polymers. In light of the above, this research is aimed at the fabrication and study of the basic mechanical properties of epoxy-resin composites filled with different weight percentages of metal filler. It includes the study of the mechanical properties of cast-iron-filler-reinforced epoxy-based polymer matrix composites. Epoxy composites containing cast iron in different weight percentages are prepared using casting technique. Data on neat epoxy are also included for comparison. All the tests were conducted at room temperature and according to ASTM standards. Density, hardness (Rockwell), tensile, flexural and impact tests were conducted, and the data were analyzed with the help of statistical charts to draw useful inferences. It was observed that the inclusion of cast iron filler affected most of the mechanical properties of neat epoxy. The density, hardness, impact strength, tensile and flexural properties of the developed composites exhibited a varying trend with respect to cast iron content. The increase in cast iron content showed significant improvement in tensile properties, hardness, impact strength and the density of the composites. The flexural strength was found to decrease at a higher cast iron content. This research also highlights the possible reasons for variation in the mechanical properties of developed polymer composites.